L'erogazione di prestazioni sanitarie in telemedicina - Francesco Burrai; Margherita Gambella; Angelica Scarpa (AboutScience Srl, 2021)
As a consequence of the Sars-CoV2 pandemic, the role of telemedicine in the healthcare sector was reviewed in order to ensure continuity of care and to contain infections. This new frontier involves professionals, caregivers, patients and can be applied in various fields, such as surgery, specialist visits, follow-ups, home care, health education, prevention and monitoring. Despite privacy may seem a deterrent for the implementation of this new goal in the healthcare sector, the community and the national legislation both provide rules to protect individuals and the community. This innovative method of assistance brings with it limits that must not detract attention from the great possibilities arising from the use of telemedicine.